THE IMPACT OF TRANSFORMATIONAL LEADERSHIP, INFRASTRUCTURE, AND PUBLIC SERVICE QUALITY ON EMPLOYEE PERFORMANCE AT THE DISTRICT PROSECUTOR'S OFFICE - Catur Wulan Anggraeni; Ellin Herlina; Abdul Aziz (International Journal of Management, Economic, Business and Accounting, 2022)
Purpose of the study — This study is to find out and examine the influence of transformational leadership, infrastructure and public service quality on employee performanceResearch method—quantitative study using quesionerResult— Transformational leadership partially affects the performance of employees of the District Prosecutor's Office of Cirebon City by 54.2%, the remaining 45.8% is influenced by other factors. The influence of infrastructure partially on the performance of employees of the District Prosecutor's Office of Cirebon City is 6.5%, the remaining 93.5% is influenced by other factors. The effect of the quality of public services partially on the performance of employees of the District Prosecutor's Office of Cirebon City is 37.7%, the remaining 62.3% is influenced by other factors. Transformational Leadership, Infrastructure and Public Service Quality have a simultaneous effect on Employee Performance. The results of the F test have a p-value of 0.000 <0.05, which means it is significant. There is the influence of Transformational Leadership, Infrastructure and Quality of Public Services simultaneously on the Performance of Employees of the District Prosecutor's Office of Cirebon City by 97.9%. The remaining 29. % is influenced by other factors.Conclusion— The study found that Transformational leadership, Infrastructure and Public Service Quality have a simultaneous positive effect on Employee Performance at the District Prosecutor's Office in Cirebon City. The combined influence of these factors is 97.9%. Practical Implications: The study suggests that implementing Transformational leadership, improving infrastructure, and enhancing Public Service Quality can lead to improved employee performance at the District Prosecutor's Office in Cirebon City. Social Implications: The study highlights the importance of good leadership, adequate resources and quality services in ensuring effective performance of public service employees. Improving employee performance at the District Prosecutor's Office can lead to better delivery of public services to the community.